Decentralization in Somaliland - Mustafe, Mahamoud Abdillahi (KIU Interdisciplinary Journal of Humanities and Social Sciences, 2024)
The main goal of decentralization is to shift power away from the national government and toward local or subnational ones. Based on the Somaliland context, this article highlights the decentralization of the administrative (de-concentration, delegation, and devolution) political, fiscal, market, and economic spheres. The literature on decentralization in Africa is the main subject of this investigation. especially Somaliland. Two times, Somaliland reclaimed its independence: first, on June 26, 1990, under British protectorate, it joins Somalia on July 1, 1960. Second it was in 18 May1991, the Somali Republic's rule was overthrown by the Somali National Movement (SNM) following a protracted battle by the Somaliland community. On 1991, Somaliland reclaimed their sovereignty. This brief history will demonstrate the various historical administrative decentralizations that Somaliland has seen, beginning in 1951 with the British Protectorate. The theoretical conceptualizations found in the literature were used as a methodology in this study. Several countries including East African nations will be used as examples in this paper, with a focus on devolution and administrative decentralization. This paper will also provide you with an additional understanding of how Somaliland upholds democracy and permits its citizens to engage and utilize their rights throughout the nation. All the points that these paper covers will base Somaliland legal framework. The various notions of decentralization, inclusive administrative decentralization, political decentralization, fiscal decentralization, market and economic decentralization, and other concepts under the key concepts are finally explained and presented in this study.